The Frequency and Antimicrobial Resistance of blaTEM and blaCTX-M Genes in Escherichia coli Isolated From Patients With a Urinary Tract Infection - Parisa Shahbazi (Zabol University of Medical sciences, 2020)
Introduction: The production of β-lactamase in bacteria, especially in Escherichia coli as a prevalent opportunistic bacterium, has caused many problems in patient treatment. β-lactamases are encoded by extended-spectrum β-lactamase (ESBL) genes such as blaTEM and blaCTX-M. We aimed to assess the prevalence and antibiotic sensitivity of β-lactamases encoded by blaCTX-M and blaTEM in E. coli isolated from patients suffering from urinary tract infections (UTIs). Methods: Escherichia coli strains were isolated from the patients’ urine culture presented to medical diagnostic laboratories in Zabol, Iran. The agar disc-diffusion test was performed on Müller-Hinton agar to investigate the antibiotic resistance of these isolates using eight antimicrobial paper discs including gentamicin, tetracycline, co-trimoxazole, norfloxacin, cefuroxime, ampicillin, neomycin, and amoxicillin. A conventional polymerase chain reaction (PCR) was used to detect blaCTX-M and blaTEM. Results: The frequencies of resistance to cefuroxime, norfloxacin, co-trimoxazole, neomycin, amoxicillin, tetracycline, gentamicin, and ampicillin were found to be 45 (90%), 15 (30%), 33 (66%), 33 (66%), 44 (88%), 34 (68%), 4 (8%), and 50 (100%), respectively. Moreover, the prevalence of blaCTX-M was 25 (50%) while that of blaTEM was 16 (32%). Conclusion: Based on the results, gentamicin and norfloxacin can be recommended as effective antibacterials for treating UTI caused by E. coli in the study population. Moreover, the frequency of resistant genes including blaCTX-M and blaTEM was high in the isolated E. coli. Effective control systems including appropriate treatments for ESBL-producing strains are therefore required for humans and food animals.